The Association of the Spatial Location of Contrast Extravasation with Symptomatic Intracranial Hemorrhage after Endovascular Therapy in Acute Ischemic Stroke Patients - Gong, Chen; Wang, You; Yuan, Jinxian; Zhang, Jie; Jiang, Shuyu; Xu, Tao; Chen, Yangmei (Current Neurovascular Research, 2023)
Background: Contrast extravasation (CE) on brain non-contrast computed tomography (NCCT) after endovascular therapy (EVT) is commonly present in patients with acute ischemic stroke (AIS). Substantial uncertainties remain about the relationship between the spatial location of CE and symptomatic intracranial hemorrhage (sICH). Therefore, this study aimed to evaluate this association. Methods: We performed a retrospective screening on consecutive patients with AIS due to LVO (AIS-LVO) who had CE on NCCT immediately after EVT for anterior circulation large vessel occlusion (LVO). We used the Alberta stroke program early CT Score (ASPECTS) scoring system to estimate the spatial location of CE. Multivariable logistic regression was performed to achieve the risk factors of sICH. Results: In this study, 115 of 153 (75.1%) anterior circulation AIS-LVO patients had CE on NCCT. After excluding 9 patients, 106 patients were enrolled in the final analysis. In multivariate regression analysis, atrial fibrillation (AF) (adjusted OR [aOR] 6.833, 95% confidence interval [CI] 1.331-35.081, P = 0.021) and CE-ASPECTS (aOR 0.602, 95% CI 0.411-0.882 P = 0.009) were associated with sICH. In subgroup analysis, CE at the internal capsule (IC) region was an independent risk factor for sICH (aOR 5.992, 95% CI 1.010-35.543 P < 0.05). These and conventional variables were incorporated as a predict model, with AUC of 0.899, demonstrating good discrimination and calibration for sICH in this study cohort. Conclusion: The spatial location of CE on NCCT immediately after EVT was an independent and strong risk factor for sICH in acute ischemic stroke patients.
Keywords: endovascular therapy